الاستفادة من بلازما الدّم في علاج كورونا المستجد (كوفيد-19): دراسة فقهيّة أصوليّة: UTILISATION OF CONVALESCENT PLASMA THERAPYFOR COVID-19 TREATMENT: A JURISTIC STUDY IN FIQH (International Seminar on Syariah and Law (INSLA), 2020)
The entire humanity is witnessing the new Corona virus pandemic (COVID-19) that has struck the most powerful nations and spread across the globe like wild fire. In the wake of endeavors to fight the virus, medical experts have employed different tools and procedures important among which is the utilization of immune blood plasma which has been proved to be effective by many clinical trials in many countries. This research seeks to reveal the Sharia position on the use of this procedure to cure COVID-19 patients particularly having regard to its importance in fighting the virus, the ignorance of many Muslims on its Sharia-compliance and absence of adequate studies on the issue. In achieving this objective, the research relies on both inductive and analytical methodologies to collect, examine, discuss and analyze the views of jurists on the issue and indicating from among such views the one that is most preponderant and compliant with the spirit and objectives of Islamic law. The most important findings of the research include: That transfusing blood plasma from a donor to a patient is not in the category of the running blood prohibited definitive authorities, because both differ in terms of meaning, attribute and effective cause; The use of blood plasma for treating the new corona virus has basis in the Sharia namely, phlebotomy and cupping; It can also be compared to blood donation and since plasma is component of blood, donating it is equally allowed under the principles of Islamic Jurisprudence. That the permissibility of transfusing blood plasma to Covid-19 patients is subject to certain conditions relating to the patients, the donor and the blood donated. يشهد البشر أجمع وباء كورونا المستجد (كوفيد-19)، الّذي عصف بأعتى الدّول، وانتشر في بلدان العالم انتشار النّار في الهشيم. وفي إطار المساعي الرّامية إلى مكافحة هذا الوباء والوقاية منه، سعى الأطبّاء لاستخدام آليّات وطرق شتّى، من أهمّها بلازما الدّم المناعيّة، الّتي أثبتت كفاءتها كثير من التّجارب السّريريّة، في العديد من دول العالم. ونظرًا لأهمّيّة هذه النّازلة في الوقاية من هذا الوباء، وجهل كثير من المسلمين بحكم الشّرع في استخدامها، وعدم وجود دراسات كافية فيها، جاء هذا البحث ليبيّن حكم الشّرع في استخدامها لعلاج المرضى المصابين بهذا الوباء. ولتحقيق هذا الهدف، اعتمد الباحث علىالمنهج الاستقرائي والمنهج التّحليلي، اللّذين يتمثّلان في استقراء وتتبّع أقوال الفقهاء والأصوليّين وأدلّتهم في هذه النّازلة، وتحليلها ومناقشتها، ثمّ التّرجيح بما يتوافق مع روح الشّريعة الإسلاميّة ومقاصدها. وقد خلص البحث إلى نتائج كثيرة، أهمّها:أنّ سحب بلازما الدّم من المتبرّع إلى المريض ليس من قبيل الدّم المسفوح المحرّم بالنّصوص القطعيّة؛ لأنّه يفارقه في  المفهوم والوصف والعلّة. أنّالاستفادة من بلازما الدّم في علاج مرضى كورونا المستجد لها أصلٌ في الشّرع، وهو الفصد والحجامة. كما أنّها تقاس على التّبرّع بالدّم؛ لأنّها جزء منه. أنّ قواعد الشّريعة الإسلاميّة الفقهيّة والأصوليّة تقتضي جواز التّبرّع بها. جواز نقل بلازما الدّم إلى المصابين بوباء كورونا المستجد2019 ينحصر في شروط، منها ما تتعلّق بالمريض، ومنها ما تتعلّق بالمتبرّع، ومنها ما تتعلّق بالدّم.